THE INFLUENCE OF ORGANIZATIONAL CULTURE, LEADERSHIP STYLE ON EMPLOYEE EXPERIENCE HAS AN IMPACT ON RETENTION - Tyas Purbasari; Ferryal Abadi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The objective of this research is to analyze the essence and influence of organizational culture and millennial employee retention, leadership styles towards organization culture, organizational culture towards employee experience, leadership styles on millennial employee experience, and the effect of employee experience as variable of strategic HRM to retain millennial employee. The research is conducted towards 226 millennial employees working in Jabodetabek and outside Jabodetabek area, between 20 – 35 years old. By using Smart PLS, this quantitative and exploratory research resulted significant impact between organizational culture and millennial employee retention, significant impact between leadership styles and organizational culture, significant impact organization culture towards millennial employee experience. This research discovered significant impact between employee experience as intervening variable of management strategic HRM to retain millennial employee. This research is an attempt to provide academic purpose for HRM strategy to retain millennial employee using new variable employee experience which is still rare to explore.